Genoprotection and Cytotoxicity of Cassia surattensis Seed Extract on Vero Cell Evaluated by Comet and Cytotoxicity Assays - Uthaya Kumar, U. Seeta; Jothy, Subramanion Lachumy; Kavitha, Nowroji; Chen, Yeng; Kanwar, Jagat Rakesh; Sasidharan, Sreenivasan (Springer India, 2018)
Cassia (C.) surattensis Burm. f. (Leguminosae) is a flowering plant that has been traditionally used in many countries for food and medicinal purposes. The present study was conducted to determine in vitro cytotoxicity and anti-genotoxic activity of the seed extract of C. surattensis. The cytotoxic and anti-genotoxic activities were evaluated against Vero cell line using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and comet assays. In vitro cytotoxicity evaluation demonstrated that seed extract of C. surattensis was non-cytotoxic against the Vero cells. The 50 % cytotoxic concentration (CC50) value from MTT cytotoxicity assay was 332.87 µg/ml. The seed extract of C. surattensis exhibited strong inhibitory effects against H2O2-mediated DNA damage in Vero cells as observed in Comet assay. The presence of antioxidant activity in the seed extract was associated with the antigenotoxic property of C. surattensis. In summary, the present study demonstrated an efficient antigenotoxic property of C. surattensis, which is significant for future investigation for human applications.